Globalization and Competitiveness in Meeting the Problems and Challenges of Education and Cultural Management SMPIT Gameel Akhlaq Bekasi - Yuwan Sari Juniarsih; Hinggil Permana (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2022)
The era of globalization full of challenges is an unavoidable period. For this reason, learning institutions, especially Islamic learning, must be able to respond to these challenges by changing the direction and orientation of learning. In experiencing the growth of the globalization era and the competitiveness of this highly environmental nation, both in terms of science and technology, it is necessary to have a defense in order to preserve the existing culture through efficient and effective learning management. SMPIT Gameel Akhlaq Bekasi has core subjects of Cultural Arts. There, students are introduced to cultural diversity because students come from different regions. On the subject of Cultural Arts, there is cultural content from many regions, this creates a sense of love for the cultural diversity of the Indonesian nation. SMPIT Gameel Akhlak Bekasi also emphasizes personality learning through tahfizh and memorizing the Qur'an, this also affects the personality of the students who want to be able to affect the management of learning and culture in schools that cannot be separated from Islamic values ​​in culture and local wisdom of citizens. so that it can print the next generation of quality and can bring Indonesia into a developed country.